Traumatic hyphaema caused by eye injuries - Łuksza, Lucyna; Homziuk, Magdalena; Nowakowska-Klimek, Marta; Glasner, Leopold; Iwaszkiewicz-Bilikiewicz, Barbara (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Hyphaema is a common consequence of mechanical ocular trauma. Blood in the anterior chamber (hyphaema) can occur after blunt or lacerating trauma. Traumatic hyphaema is a diagnostic and therapeutic emergency. Major complications of hyphaema include secondary hemorrhage, secondary glaucoma, corneal staining and disturbances in visual acuity. The aim of our study was the retrospective analysis of patients with posttraumatic hyphaema. According to a prospective protocol we studied 428 patients who were examined and treated at the Emergency Department of Department of Ophthalmology Medical University of Gdansk between 1998-2004 years (ears). Data obtained included age and sex. 81% of patients were man, 19% of patients were women. Mean age of patients with ocular hyphaema 6-72 years. We determined initial and final visual acuities (isual acuity – distance Snellen acuity test), intraocular pressure measurement, biomicroscopy, fundus indirect ophthalmology, gonioscopy and US- examinations (sometimes). Data obtained also were: slitlamp examinations for hyphaema size, hyphaema grading and corneal clarity. Most hyphaemas were small, occupying less than one- third of the volume of the anterior chamber. The most common associated injuries to the eye hyphaema included corneal oedema, glaucoma (secondary glaucoma), cataract and mydriasis. Traumatic hyphaema is therapeutic emergency. More preventive efforts (hospitalization) were necessary, especially for children. In our study we observed 89% patients with traumatic hyphaema due to non – penetrating eye injury. The assault were responsible for hyphaema in 30.1% of cases and traffic accidents in 38.7% of all hyphaemas. Treatment of the hyphaema is generally topical. Outcome is good (in more cases), if medical treatment was quickly instituted. Surgical treatment must be reserved for a special cases, but it needs more further investigations.